Community Transformation Through Mosque-Based Empowerment in Amplas Village Kota Medan - Cahyanti, Fifi; Yulia, Fatma (LP2M INSURI Ponorogo, 2024)
Seeing the phenomenon that occurs, there is a lack of public awareness regarding mosque-based empowerment. The people there consider the mosque only a place of worship. This research aims to determine the level of pb;ic awarenessof the function of the mosque, which is not only a place of worship for muslims but also for activities related to the Islamic religion in the amplas sub-district, Medan city. The method that the researcher used was qualititave descriptive method in which the researcher conducted observation interviews and documentation related to the problem. The results of the research show that many people still thinkthat mosques are only places of worship, even in the amplas sub-district of Medan city, religious studies, recitations are held, as well as various social and humanitarian activities such as donations and social service. Initially they agreed with this, but over time the community became inconsistent in doing things related to the mosque. There are several factors that cause people to be unable to take part in these social activities over time, including being busy with their respective jobs.